2018
DOI: 10.21608/aps.2018.18735
|View full text |Cite
|
Sign up to set email alerts
|

The anti-anemic effect of dried beet green in phenylhydrazine treated rats

Abstract: Phenylhydrazine (PHZ) and its derivatives were used firstly as antipyretics but the toxic action on red blood cells made their use dangerous. The aim of this study was to estimate the contents of iron and vitamins in different parts of beetroot as root and beet green (leave and stalk together) as well as their ethanol extracts. Then, the biochemical evaluation for the highest iron and vitamins contents as an anti-anemic effect against anemic rats caused by phenylhydrazine were studied. Anemia induction caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…On the other hand, the study showed after 20 days taking 8 g of beetroot the level of total iron binding capacity decreased and serum iron levels increased. This indicates that beetroot is an excellent source of iron [27]. 1a, b, c, d, e, significantly different from negative or positive control at p<0.05.…”
Section: Effect On Iron Ferritin and Ascorbic Acidmentioning
confidence: 80%
See 3 more Smart Citations
“…On the other hand, the study showed after 20 days taking 8 g of beetroot the level of total iron binding capacity decreased and serum iron levels increased. This indicates that beetroot is an excellent source of iron [27]. 1a, b, c, d, e, significantly different from negative or positive control at p<0.05.…”
Section: Effect On Iron Ferritin and Ascorbic Acidmentioning
confidence: 80%
“…Also, vitamin B6 and B12 were in values of 5.46 and 54.48 mg /100g in beetroot compared to 0.081 and 0.00 mg /100g in eggplant, respectively as seen in table 1. Dried beet green has been a rich source of vitamins B6, B12, and folic acid [27]. The chemical composition of this part was estimated to prepare a diet to reduce anemia caused by PHZ in rats, anti-anemic effect of dried beet green in phenylhydrazine treated rats was approved Elaby and Ali., 2018 [27].…”
Section: Chemical Composition Of Raw Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenylhydrazine-induced erythropenia lowered Hb and reduced HCT levels which persisted for 8–12 days [ 13 ]. Furthermore, phenylhydrazine also induces pathological changes in tissues such as heart, kidney, liver and spleen [ 16 ]. Therefore to screen the antianemic potential of RK, we evaluated levels of RBCs, Hb and HCT during experimental period as well as histopathological studies of major organs at the end of experimental period.…”
Section: Discussionmentioning
confidence: 99%